Effect of aging on structure and shape memory behavior of a Cu-Al-Mn-Ti-C shape memory alloy - Yildiz, Koksal (Elsevier, 2020)
Effects of aging on the microstructure, structural properties, phase components, transformation characteristics and shape memory behavior of the Cu-12Al-3Mn-0.7Ti-0.3C (wt.%) SMA have been investigated by means of SEM, XRD, DSC measurements and the bending test. The results indicate that properties of the alloy depends strongly on aging temperatures performed at 300 degrees C, 400 degrees C and 500 degrees C for 30 minutes. While the alloy sample aged at 300 degrees C has generally similar properties with the base alloy sample, as the aging temperature increases, significant changes have occurred in the microstructural properties of the alloy. After aging at 500 degrees C, alpha-phase precipitated as a result of beta phase decomposition and micro voids formed in the microstructure of the alloy. It is found that these obstacles give rise to the expansion of the transformation hysteresis value of 289.3 degrees C for the sample aged at 500 degrees C by affecting transformation temperatures, the change of the thermodynamic parameters and also a decrease in shape recovery ratio of 50% of the alloy.
Keywords: Cu-based SMA; shape-memory materials; aging; martensitic transformation; shape memory effect